Valence tautomerism of p-block element compounds: an eligible phenomenon for main group catalysis? - Greb, Lutz (European journal of inorganic chemistry, 2022)
Valence tautomerism has had a remarkable impact on several branches of transition metal chemistry. By switching between different valence tautomeric states, physicochemical properties and reactivities can be triggered reversibly. Is this phenomenon transferrable into the p-block - or is it already happening there? This Perspective collects observations of p-block element-ligand systems that might be assignable to valence tautomerism. Further, it discusses occurrences in p-block element compounds that exhibit the related effect of redox-induced electron transfer. As disclosed, the concept of valence tautomerism with p-block elements is at a very early stage. However, given the substantial disparity in the properties of those elements in different redox states, it might offer a valid extension for future developments in main group catalysis.
First published: 29 December 2021
Gesehen am 30.05.2022